The Influence of Health Education and Simulation Methods on The Improvement of Mother’s Knowledge and Skill in Handling Injury Toward Children at Home - Abd. Hady J; Andi Agustang; Arlin Adam; Simunati Simunati; Hariani Hariani; Nuraeni Mustari (Journal of Global Pharma Technology, 2020)
This research aimed to analyze the influence of providing health education and simulation method on the mothers’s knowledge and skill in handling first aid toward children at home. This research was a quasi-experimental research by utilizing two group pretest-posttest design. The sample size were 65 mothers, selected using purposive sampling. Data collection was carried out in the pre test and post test phases. In this case, the data were collected through questionnaires, observations and interviews. After the data has been collected, then analyzed using paired sample t-test. Regarding the knowledge, the statistical test result was obtained p-value of 0.000 (